Heat-conducting composite lubricating oil and preparation method thereof

By adding modification additives and modified fillers to the lubricant and reacting under specific conditions to generate polyurea grease, the existing lubricant oil has been solved, and better thermal conductivity and lubricating performance have been achieved.

CN119614269AActive Publication Date: 2025-03-14DONGGUAN ESMAN LUBRICA TING TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411654205.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-14
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

During use, the existing lubricating oil causes thermal oxidation of the oil film due to the heat released by friction, thereby reducing the lubricating effect and poor thermal conductivity.

Method used

By using the preparation method of thermally conductive composite lubricating oil, the base oil, modified additive, octadecyl primary amine, cyclohexylamine, diphenylmethane diisocyanate and modified filler are blended, and the reaction is carried out under specific conditions to generate polyurea grease and modified filler, thereby improving the thermal conductivity of the lubricating oil.

Benefits of technology

It improves the thermal conductivity and lubricating performance of lubricating oil, extends the service life of lubricating oil, and avoids the reduction in lubricating effect caused by thermal oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses heat-conducting compound lubricating oil and a preparation method thereof.The heat-conducting compound lubricating oil is prepared from, by weight, 500-600 parts of base oil, 5-10 parts of modified additive, 10-15 parts of octadecyl primary amine, 20-30 parts of cyclohexylamine, 40-50 parts of diphenylmethane diisocyanate and 20-25 parts of modified filler. The bond energy of a carbon-sulfur bond in the modified additive is small, so that the carbon-sulfur bond is broken, sulfide containing an organic silicon chain segment is generated and is combined with the metal surface to form a ferric sulfate film, meanwhile, the film contains an organic silicon component, the antirust effect of the metal contact surface can be improved, benzotriazole generated by breaking can also be coordinated with metal ions, and the antirust effect of the metal surface is improved. And by adding the modified filler, heat generated by friction can be rapidly conducted, and the problem that the lubricating effect is reduced due to thermal aging of the lubricating oil on the surface is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating oil preparation, and in particular to a heat-conducting composite lubricating oil and a preparation method thereof. Background Art

[0002] Lubricating oil is a liquid or semi-solid lubricant used in automobiles and mechanical equipment to reduce friction and protect machinery and processed parts. It mainly plays the role of lubrication, cooling, rust prevention, cleaning, sealing and buffering. Lubricating oil is composed of two parts: base oil and additives. Base oil is the main component of lubricating oil and determines the basic properties of lubricating oil. Additives can make up for and improve the deficiencies in the performance of base oil and give it some new properties. It is an important component of lubricating oil. During the use of existing lubricating oil, a large amount of heat is released due to friction. The heat accumulates inside the oil film, causing thermal oxidation of the oil film, which in turn causes the lubricating effect of the lubricating oil to decrease or even disappear, seriously affecting the normal use of the lubricating oil. Summary of the invention

[0003] The purpose of the present invention is to provide a heat-conducting composite lubricating oil and a preparation method thereof, which solves the problem that the current lubricating oil has a general lubricating effect and a poor heat-conducting effect.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a heat-conducting composite lubricating oil specifically comprises the following steps: The following raw materials are weighed in parts by weight: 500-600 parts of base oil, 5-10 parts of modified additives, 10-15 parts of octadecyl primary amine, 20-30 parts of cyclohexylamine, 40-50 parts of diphenylmethane diisocyanate and 20-25 parts of modified filler, the base oil, diphenylmethane diisocyanate and modified filler are mixed, and stirred for 20-30 minutes at a speed of 300-500 r / min and a temperature of 60-65° C., octadecyl primary amine and cyclohexylamine are added, the temperature is raised to 90-100° C., the reaction is carried out for 40-50 minutes, the temperature is raised to 150-160° C., and after keeping the temperature for 3-5 hours, the temperature is lowered to 70-80° C., the modified additive is added, and the mixture is stirred evenly to obtain a thermal conductive composite lubricating oil.

[0005] Further, the modified additive is prepared by the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 90-95° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, 1,2-epoxyhexadecane and DMF are uniformly mixed, and the reaction is carried out for 6-8 hours at a speed of 150-200 r / min, a temperature of 40-50° C. and a pH value of 9-10 to obtain an intermediate 1; Step A2: Intermediate 1, mercaptophenylboric acid and DMF are mixed uniformly, stirred and magnesium sulfate is added at a speed of 120-150 r / min and a temperature of 25-30° C., and the reaction is carried out for 20-25 hours to obtain intermediate 2; intermediate 2, acrylic acid, dimethylphenylphosphine and DMF are mixed uniformly, and the reaction is carried out for 1-1.5 hours at a speed of 60-80 r / min, a temperature of 60-70° C. and irradiation with 365 nm ultraviolet light to obtain intermediate 3; Step A3: Mix methylbenzotriazole, 2-aminoethanol, formaldehyde and anhydrous ethanol evenly, and react at a speed of 150-200 r / min and a temperature of 80-85°C for 7-8h to obtain a modifier; mix intermediate 3, the modifier, p-toluenesulfonic acid and toluene evenly, and react at a speed of 120-150 r / min and a temperature of 110-120°C for 6-8h to obtain a modified additive.

[0006] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A1 is 2:1.5:1, and the molar ratio of diamine-terminated polysiloxane and 1,2-epoxyhexadecane is 1:2.

[0007] Furthermore, the amount ratio of intermediate 1, mercaptophenylboric acid and magnesium sulfate in step A2 is 15mmol:30mmol:5g, the molar ratio of intermediate 2 and acrylic acid is 1:2, and the amount of dimethylphenylphosphine is 5‰ of the mass of acrylic acid.

[0008] Furthermore, the molar ratio of methylbenzotriazole, 2-aminoethanol and formaldehyde in step A3 is 2:1:2.1, the molar ratio of intermediate 3 and modifier is 1:2, and the amount of p-toluenesulfonic acid is 1% of the mass of the modifier.

[0009] Further, the modified filler is prepared by the following steps: Boron nitride and sodium hydroxide aqueous solution are mixed, ball-milled for 24 hours at a rotation speed of 200 r / min, and then the supernatant is removed by centrifugation. The substrate is washed with a hydrochloric acid solution until it is neutral to obtain hydroxylated boron nitride. Graphene oxide, hydroxylated boron nitride, concentrated sulfuric acid and toluene are evenly mixed, and reacted for 6-8 hours at a rotation speed of 60-80 r / min and a temperature of 110-120° C. to obtain a composite material. The composite material is dispersed in ethanol, stirred at a rotation speed of 150-200 r / min and a temperature of 40-50° C., and KH550 and deionized water are added to react for 3-5 hours to obtain a modified filler.

[0010] Furthermore, the usage ratio of the boron nitride and the sodium hydroxide aqueous solution is 1 g:50 mL, the concentration of the sodium hydroxide aqueous solution is 2 mol / L, the usage ratio of graphene oxide, hydroxyboron nitride and concentrated sulfuric acid is 5 g:1 g:3 mL, and the usage of KH550 is 1‰ of the mass of the composite material.

[0011] Beneficial effects of the present invention: A thermally conductive composite lubricant disclosed in the present invention comprises the following raw materials: base oil, a modified additive, octadecyl primary amine, cyclohexylamine, diphenylmethane diisocyanate and a modified filler. During the raw material blending process, octadecyl primary amine, cyclohexylamine and diphenylmethane diisocyanate react to produce polyurea to form a polyurea grease. The surface amino group of the modified filler can participate in the reaction of the polyurea, thereby increasing the dispersibility of the modified filler and increasing the degree of polyurea branching.

[0012] The modified additive is prepared by ring-opening octamethylcyclotetrasiloxane as a raw material, and then polymerizing with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain a diamine-terminated polysiloxane. The diamine-terminated polysiloxane is reacted with 1,2-epoxyhexadecane to make the amino group on the diamine-terminated polysiloxane react with the epoxy group on the 1,2-epoxyhexadecane to obtain an intermediate 1. The intermediate 1 is reacted with mercaptophenylboronic acid to make the hydroxyl group of the intermediate 1 react with the boric acid group on the mercaptoboric acid ester. The borate ester is formed by reaction to obtain intermediate 2, intermediate 2 and acrylic acid are reacted under ultraviolet light to graft the thiol group on intermediate 2 with the double bond on acrylic acid to obtain intermediate 3, methylbenzotriazole, 2-aminoethanol and formaldehyde are reacted to react the secondary amine on methylbenzotriazole and the amino group on 2-aminoethanol with the aldehyde group to obtain a modifier, the modifier is reacted with intermediate 3 to esterify the hydroxyl group on the modifier with the carboxyl group on intermediate 3 to obtain a modified additive.

[0013] The modified filler is prepared by treating boron nitride as a raw material with an aqueous sodium hydroxide solution so that hydroxyl groups are grafted onto the surface of the boron nitride to obtain hydroxylated boron nitride. Graphene oxide and hydroxylated boron nitride are treated with concentrated sulfuric acid so that carboxyl groups on the graphene oxide and hydroxyl groups on the hydroxylated boron nitride are esterified to obtain a composite material. The composite material is treated with KH550 so that amino groups are grafted onto the surface to obtain a modified filler.

[0014] During the use of lubricating oil, friction occurs, and the bond energy of the carbon-sulfur bond in the modified additive is small, so it breaks, producing sulfides containing silicone segments, which combine with the metal surface to form an iron sulfate film. At the same time, the film contains silicone components that can increase the anti-rust effect of the metal contact surface. The benzotriazole produced by the break can also coordinate with metal ions, thereby enhancing the protection of the lubricating oil on the metal surface. The addition of modified fillers can quickly conduct the heat generated by friction, effectively solving the problem of reduced lubrication effect of the surface lubricant due to thermal aging. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0016] A method for preparing a heat-conducting composite lubricating oil specifically comprises the following steps: The following raw materials were weighed in parts by weight: 500 parts of base oil, 5 parts of modified additives, 10 parts of octadecyl primary amine, 20 parts of cyclohexylamine, 40 parts of diphenylmethane diisocyanate and 20 parts of modified fillers. The base oil, diphenylmethane diisocyanate and modified filler were mixed, and stirred at a speed of 300 r / min and a temperature of 60° C. for 20 minutes. Then, octadecyl primary amine and cyclohexylamine were added, the temperature was raised to 90° C., and the reaction was carried out for 40 minutes. The temperature was raised to 150° C. and kept warm for 3 hours. Then, the temperature was lowered to 70° C., the modified additive was added, and the mixture was stirred evenly to obtain a thermally conductive composite lubricating oil.

[0017] The model of the base oil is 150N.

[0018] The modified additive is prepared by the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 3 hours at a speed of 120 r / min and a temperature of 90° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, 1,2-epoxyhexadecane and DMF are mixed uniformly, and the mixture is reacted for 6 hours at a speed of 150 r / min, a temperature of 40° C. and a pH value of 9 to obtain an intermediate 1; Step A2: Intermediate 1, mercaptophenylboric acid and DMF were mixed evenly, stirred and magnesium sulfate was added at a speed of 120 r / min and a temperature of 25° C., and the mixture was reacted for 20 h to obtain Intermediate 2; Intermediate 2, acrylic acid, dimethylphenylphosphine and DMF were mixed evenly, and the mixture was reacted at a speed of 60 r / min, a temperature of 60° C. and irradiated with 365 nm ultraviolet light for 1 h to obtain Intermediate 3; Step A3: Mix methylbenzotriazole, 2-aminoethanol, formaldehyde and anhydrous ethanol evenly, and react at a speed of 150 r / min and a temperature of 80°C for 7 hours to obtain a modifier. Mix intermediate 3, the modifier, p-toluenesulfonic acid and toluene evenly, and react at a speed of 120 r / min and a temperature of 110°C for 6 hours to obtain a modified additive.

[0019] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A1 is 2:1.5:1, and the molar ratio of diamine-terminated polysiloxane and 1,2-epoxyhexadecane is 1:2.

[0020] The amount ratio of intermediate 1, mercaptophenylboric acid and magnesium sulfate in step A2 is 15mmol:30mmol:5g, the molar ratio of intermediate 2 and acrylic acid is 1:2, and the amount of dimethylphenylphosphine is 5‰ of the mass of acrylic acid.

[0021] The molar ratio of methylbenzotriazole, 2-aminoethanol and formaldehyde in step A3 is 2:1:2.1, the molar ratio of intermediate 3 and modifier is 1:2, and the amount of p-toluenesulfonic acid is 1% of the mass of the modifier.

[0022] The modified filler is prepared by the following steps: Boron nitride and sodium hydroxide aqueous solution were mixed, ball-milled for 24 hours at a rotation speed of 200 r / min, and the supernatant was removed by centrifugation. The substrate was washed with hydrochloric acid solution until neutral to obtain hydroxylated boron nitride. Graphene oxide, hydroxylated boron nitride, concentrated sulfuric acid and toluene were evenly mixed, and reacted for 6 hours at a rotation speed of 60 r / min and a temperature of 110°C to obtain a composite material. The composite material was dispersed in ethanol, stirred at a rotation speed of 150 r / min and a temperature of 40°C, and KH550 and deionized water were added to react for 3 hours to obtain a modified filler.

[0023] The dosage ratio of the boron nitride and the sodium hydroxide aqueous solution is 1g:50mL, the concentration of the sodium hydroxide aqueous solution is 2mol / L, the dosage ratio of graphene oxide, hydroxyboron nitride and concentrated sulfuric acid is 5g:1g:3mL, and the dosage of KH550 is 1‰ of the mass of the composite material. Example

[0024] A method for preparing a heat-conducting composite lubricating oil specifically comprises the following steps: The following raw materials were weighed in parts by weight: 550 parts of base oil, 8 parts of modified additives, 13 parts of octadecyl primary amine, 25 parts of cyclohexylamine, 45 parts of diphenylmethane diisocyanate and 25 parts of modified filler. The base oil, diphenylmethane diisocyanate and modified filler were mixed, stirred at a speed of 300 r / min and a temperature of 60°C for 25 minutes, octadecyl primary amine and cyclohexylamine were added, the temperature was raised to 95°C, the reaction was carried out for 45 minutes, the temperature was raised to 155°C, the temperature was kept for 4 hours, the temperature was lowered to 75°C, the modified additive was added, and the mixture was stirred evenly to obtain a thermally conductive composite lubricating oil.

[0025] The type of the base oil is 150SN.

[0026] The modified additive is prepared by the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 4 hours at a speed of 120 r / min and a temperature of 95° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, 1,2-epoxyhexadecane and DMF are mixed uniformly, and the mixture is reacted for 7 hours at a speed of 150 r / min, a temperature of 50° C. and a pH value of 9 to obtain an intermediate 1; Step A2: Intermediate 1, mercaptophenylboric acid and DMF were mixed evenly, stirred and magnesium sulfate was added at a speed of 150 r / min and a temperature of 25° C., and the reaction was carried out for 25 hours to obtain intermediate 2; intermediate 2, acrylic acid, dimethylphenylphosphine and DMF were mixed evenly, and the reaction was carried out at a speed of 60 r / min, a temperature of 65° C. and irradiation with 365 nm ultraviolet light for 1.5 hours to obtain intermediate 3; Step A3: Mix methylbenzotriazole, 2-aminoethanol, formaldehyde and anhydrous ethanol evenly, and react at a speed of 150 r / min and a temperature of 85°C for 7.5 hours to obtain a modifier; mix intermediate 3, the modifier, p-toluenesulfonic acid and toluene evenly, and react at a speed of 120 r / min and a temperature of 115°C for 7 hours to obtain a modified additive.

[0027] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A1 is 2:1.5:1, and the molar ratio of diamine-terminated polysiloxane and 1,2-epoxyhexadecane is 1:2.

[0028] The amount ratio of intermediate 1, mercaptophenylboric acid and magnesium sulfate in step A2 is 15mmol:30mmol:5g, the molar ratio of intermediate 2 and acrylic acid is 1:2, and the amount of dimethylphenylphosphine is 5‰ of the mass of acrylic acid.

[0029] The molar ratio of methylbenzotriazole, 2-aminoethanol and formaldehyde in step A3 is 2:1:2.1, the molar ratio of intermediate 3 and modifier is 1:2, and the amount of p-toluenesulfonic acid is 1% of the mass of the modifier.

[0030] The modified filler is prepared by the following steps: Boron nitride and sodium hydroxide aqueous solution were mixed, ball-milled for 24 hours at a rotation speed of 200 r / min, and the supernatant was removed by centrifugation. The substrate was washed with hydrochloric acid solution until neutral to obtain hydroxylated boron nitride. Graphene oxide, hydroxylated boron nitride, concentrated sulfuric acid and toluene were mixed evenly, reacted for 7 hours at a rotation speed of 80 r / min and a temperature of 115°C to obtain a composite material. The composite material was dispersed in ethanol, stirred at a rotation speed of 150 r / min and a temperature of 45°C, and KH550 and deionized water were added to react for 4 hours to obtain a modified filler.

[0031] The dosage ratio of the boron nitride and the sodium hydroxide aqueous solution is 1g:50mL, the concentration of the sodium hydroxide aqueous solution is 2mol / L, the dosage ratio of graphene oxide, hydroxyboron nitride and concentrated sulfuric acid is 5g:1g:3mL, and the dosage of KH550 is 1‰ of the mass of the composite material. Example

[0032] A method for preparing a heat-conducting composite lubricating oil specifically comprises the following steps: The following raw materials were weighed in parts by weight: 600 parts of base oil, 10 parts of modifying additive, 15 parts of octadecyl primary amine, 30 parts of cyclohexylamine, 50 parts of diphenylmethane diisocyanate and 25 parts of modified filler. The base oil, diphenylmethane diisocyanate and modified filler were mixed, stirred at a speed of 500 r / min and a temperature of 65°C for 30 minutes, octadecyl primary amine and cyclohexylamine were added, the temperature was raised to 100°C, the reaction was carried out for 50 minutes, the temperature was raised to 160°C, and the temperature was kept for 5 hours, then the temperature was lowered to 80°C, the modifying additive was added, and the mixture was stirred evenly to obtain a thermal conductive composite lubricating oil.

[0033] The model of the base oil is 250SN.

[0034] The modified additive is prepared by the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 5 hours at a speed of 150 r / min and a temperature of 95° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, 1,2-epoxyhexadecane and DMF are mixed uniformly, and the mixture is reacted for 8 hours at a speed of 200 r / min, a temperature of 50° C. and a pH value of 10 to obtain an intermediate 1; Step A2: Intermediate 1, mercaptophenylboric acid and DMF were mixed evenly, stirred and magnesium sulfate was added at a speed of 150 r / min and a temperature of 30° C., and the mixture was reacted for 25 h to obtain Intermediate 2; Intermediate 2, acrylic acid, dimethylphenylphosphine and DMF were mixed evenly, and the mixture was reacted at a speed of 80 r / min, a temperature of 70° C. and irradiated with 365 nm ultraviolet light for 1.5 h to obtain Intermediate 3; Step A3: Mix methylbenzotriazole, 2-aminoethanol, formaldehyde and anhydrous ethanol evenly, and react at a speed of 200 r / min and a temperature of 85°C for 8 hours to obtain a modifier. Mix intermediate 3, the modifier, p-toluenesulfonic acid and toluene evenly, and react at a speed of 150 r / min and a temperature of 120°C for 8 hours to obtain a modified additive.

[0035] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A1 is 2:1.5:1, and the molar ratio of diamine-terminated polysiloxane and 1,2-epoxyhexadecane is 1:2.

[0036] The amount ratio of intermediate 1, mercaptophenylboric acid and magnesium sulfate in step A2 is 15mmol:30mmol:5g, the molar ratio of intermediate 2 and acrylic acid is 1:2, and the amount of dimethylphenylphosphine is 5‰ of the mass of acrylic acid.

[0037] The molar ratio of methylbenzotriazole, 2-aminoethanol and formaldehyde in step A3 is 2:1:2.1, the molar ratio of intermediate 3 and modifier is 1:2, and the amount of p-toluenesulfonic acid is 1% of the mass of the modifier.

[0038] The modified filler is prepared by the following steps: Boron nitride and sodium hydroxide aqueous solution were mixed, ball-milled for 24 hours at a speed of 200 r / min, and the supernatant was removed by centrifugation. The substrate was washed with a hydrochloric acid solution until it was neutral to obtain hydroxylated boron nitride. Graphene oxide, hydroxylated boron nitride, concentrated sulfuric acid and toluene were mixed evenly, reacted for 8 hours at a speed of 80 r / min and a temperature of 120°C to obtain a composite material. The composite material was dispersed in ethanol, stirred at a speed of 200 r / min and a temperature of 50°C, and KH550 and deionized water were added to react for 5 hours to obtain a modified filler.

[0039] The dosage ratio of the boron nitride and the sodium hydroxide aqueous solution is 1g:50mL, the concentration of the sodium hydroxide aqueous solution is 2mol / L, the dosage ratio of graphene oxide, hydroxyboron nitride and concentrated sulfuric acid is 5g:1g:3mL, and the dosage of KH550 is 1‰ of the mass of the composite material.

[0040] Comparative Example 1 Compared with Example 1, propylene oxide was used to replace 1,2-epoxyhexadecane in this comparative example, and the other steps were the same.

[0041] Comparative Example 2 Compared with Example 1, this comparative example uses ethylenediamine instead of diamine-terminated polysiloxane, and the remaining steps are the same.

[0042] Comparative Example 3 Compared with Example 1, this comparative example uses intermediate 3 to replace the modified additive, and the remaining steps are the same.

[0043] Comparative Example 4 Compared with Example 1, this comparative example uses graphene instead of the modified filler, and the remaining steps are the same.

[0044] Comparative Example 5 Compared with Example 1, this comparative example uses boron nitride to replace the modified filler, and the other steps are the same.

[0045] The lubricating oil samples obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to friction and wear tests using a four-ball friction tester. Precision bearing steel balls with a diameter of 12.7 mm and a material of Gcr15 were selected as friction balls. Under the conditions of a load of 392 N and a rotation speed of 1200 r / min, the friction was carried out for 30 minutes to obtain the friction coefficient and wear spot diameter. The thermal conductivity was tested using a thermal conductivity tester. The test results are shown in the following table.

[0046]

[0047] It can be seen from the above table that the present application has good lubrication effect and heat conduction effect.

[0048] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a heat-conducting composite lubricating oil, characterized in that: The specific steps include: The following raw materials are weighed in parts by weight: 500-600 parts of base oil, 5-10 parts of modified additives, 10-15 parts of octadecyl primary amine, 20-30 parts of cyclohexylamine, 40-50 parts of diphenylmethane diisocyanate and 20-25 parts of modified filler. After mixing the base oil, diphenylmethane diisocyanate and modified filler, octadecyl primary amine and cyclohexylamine are added to react, and then the modified additive is added and stirred evenly to obtain a thermal conductive composite lubricating oil.

2. The method for preparing a heat-conducting composite lubricating oil according to claim 1, characterized in that: The modified additive is prepared by the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the mixture is reacted to obtain diamine-terminated polysiloxane, and the diamine-terminated polysiloxane, 1,2-epoxyhexadecane and DMF are mixed for reaction to obtain intermediate 1; Step A2: Mix and stir the intermediate 1, mercaptophenylboronic acid and DMF, add magnesium sulfate and react to obtain the intermediate 2; mix and react the intermediate 2, acrylic acid, dimethylphenylphosphine and DMF to obtain the intermediate 3; Step A3: methylbenzotriazole, 2-aminoethanol, formaldehyde and anhydrous ethanol are mixed and reacted to obtain a modifier, and the intermediate 3, the modifier, p-toluenesulfonic acid and toluene are mixed and reacted to obtain a modified additive.

3. The method for preparing a heat-conducting composite lubricating oil according to claim 2, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A1 is 2:1.5:1, and the molar ratio of diamine-terminated polysiloxane and 1,2-epoxyhexadecane is 1:

2.

4. The method for preparing a heat-conducting composite lubricating oil according to claim 2, characterized in that: The usage ratio of intermediate 1, mercaptophenylboric acid and magnesium sulfate in step A2 is 15mmol:30mmol:5g, and the molar ratio of intermediate 2 and acrylic acid is 1:

2.

5. The method for preparing a heat-conducting composite lubricating oil according to claim 2, characterized in that: The molar ratio of methylbenzotriazole, 2-aminoethanol and formaldehyde in step A3 is 2:1:2.1, and the molar ratio of intermediate 3 and modifier is 1:

2.

6. The method for preparing a heat-conducting composite lubricating oil according to claim 1, characterized in that: The modified filler is prepared by the following steps: Boron nitride and sodium hydroxide aqueous solution are mixed and ball-milled, and the supernatant is removed by centrifugation. The substrate is washed with a hydrochloric acid solution until it is neutral to obtain hydroxylated boron nitride. Graphene oxide, hydroxylated boron nitride, concentrated sulfuric acid and toluene are mixed and reacted to obtain a composite material. The composite material is dispersed in ethanol, stirred, and KH550 and deionized water are added to react to obtain a modified filler.

7. The method for preparing a heat-conducting composite lubricating oil according to claim 6, characterized in that: The dosage ratio of the boron nitride and the sodium hydroxide aqueous solution is 1g:50mL, the dosage ratio of graphene oxide, hydroxyboron nitride and concentrated sulfuric acid is 5g:1g:3mL, and the dosage of KH550 is 1‰ of the mass of the composite material.

8. A heat-conducting composite lubricating oil, characterized in that: Prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Lubricating grease for automobile constant velocity universal joint

    CN116925833A

  • Anti-corrosion lining material for high-temperature-resistant and wear-resistant pipeline and preparation method of anti-corrosion lining material

    CN118546450A

  • Flame-retardant ABS alloy material and preparation method thereof

    CN118852834A

  • Modified boron nitride, composite material containing same, preparation method therefor, and application thereof

    WO2023274068A1